1993
DOI: 10.1001/archsurg.1993.01420150027005
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Electrolyte Secretion

Abstract: The contemporary paradigm for active chloride secretion by vertebrate epithelial cells evolved, at least in part, from experiments that began in the laboratory of Dr William Silen at Beth Israel Hospital in Boston, Mass. It was first shown there that cyclic adenosine monophosphate and cholera toxin stimulate active chloride secretion when added to intestinal mucosa in vitro. The paradigm, which evolved further from experiments on shark rectal gland and flounder intestine at the Mt Desert Island Biological Labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…measured the rectal PD in UC patients sequentially and found that the rectal PD became positive during acute flare‐ups, followed by recovery to negative values during the healing phase 7 . At the time, this was interpreted exclusively as a loss of active Na + resorption, because it was not widely recognized yet that the intestinal mucosa also secreted Cl − in an electrogenic fashion 8 …”
Section: Early Studies In Intestinal Ion Transport Properties In Patimentioning
confidence: 99%
“…measured the rectal PD in UC patients sequentially and found that the rectal PD became positive during acute flare‐ups, followed by recovery to negative values during the healing phase 7 . At the time, this was interpreted exclusively as a loss of active Na + resorption, because it was not widely recognized yet that the intestinal mucosa also secreted Cl − in an electrogenic fashion 8 …”
Section: Early Studies In Intestinal Ion Transport Properties In Patimentioning
confidence: 99%
“…It is generally accepted that these important fluid transfers are associated with salt reabsorption or secretion. Nevertheless, it is still a subject of controversy whether the absorptive processes are located in the surface (and villus) cells, if the secretory processes are located in the crypt cells (4,5) and if the transport-associated water movements are transcellular or paracellular (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of transepithelial secretion of fluid and electrolytes in the intestine have historically led the way to our understanding of basic concepts of this important physiological process and its associated pathophysiology (18). It is well known that cAMP-mediated agonists, and Vibrio cholera toxin, are able to elicit CFTR-mediated chloride secretion.…”
Section: Intestinal Epithelium Caccsmentioning
confidence: 99%